2023
DOI: 10.1186/s12889-023-15130-y
|View full text |Cite
|
Sign up to set email alerts
|

Changing incidence of hepatitis B and persistent infection risk in adults: a population-based follow-up study from 2011 in China

Abstract: Background This study aimed to estimate hepatitis B incidence and chronicity risk in rural adults in China under the background of eliminating viral hepatitis. Methods Hepatitis B surface antigen (HBsAg) screening was conducted every 2 years in demonstration areas since 2011. Individuals with baseline HBsAg-negative were included. Incidence was calculated as the number of HBsAg-positive cases divided by the total person-times. HBsAg-positive indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Consistent with previous research, our findings revealed significant period effects 9 11 , 21 . The incidence of acute hepatitis B decreased significantly over time, while that of chronic hepatitis B remained stable in recent years.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous research, our findings revealed significant period effects 9 11 , 21 . The incidence of acute hepatitis B decreased significantly over time, while that of chronic hepatitis B remained stable in recent years.…”
Section: Discussionsupporting
confidence: 93%
“…We attribute this to hepatitis B vaccination coverage and prevention of mother-to-child transmission of hepatitis B virus 22 . For instance, according to laboratory surveillance data in England, the HB incidence decreased from 7.4/100,000 in 1995–2000 to 1.1/100,000 in 2008, representing an 85% reduction 11 . In China, the plasma-derived hepatitis B vaccine (HepB) was licensed in 1985.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2012, universal screening for HBsAg in pregnant women has been implemented per national policy in China, leading to improved detection and treatment rates for women [45]. Previously, it was shown that males had a higher risk of contracting HBV [46]. Other investigations on sex and risk of HBV attributed to males relatively greater exposure to sexually transmitted risk factors, such as men who have sex with men and persons with multiple sexual partners to increased prevalence of HBV compared to females [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Approximating the Asian population as 20,000 individuals with an HBsAg prevalence of 8.5% and precision of 5.0%, the required number to screen is 119. 8 , 9 , 10 …”
Section: Methodsmentioning
confidence: 99%